The serotonin 5-HT3 receptor: a novel neurodevelopmental target - Engel, Mareen; Smidt, Marten P.; Van Hooft, Johannes A. (Frontiers in Cellular Neuroscience, 2013)
Serotonin (5-HT), next to being an important neurotransmitter, recently gained attention as a key regulator of pre- and postnatal development in the mammalian central nervous system (CNS). Several receptors for 5-HT are expressed in the developing brain including a ligand-gated ion channel, the 5-HT3 receptor. Over the past years, evidence has been accumulating that 5-HT3 receptors are involved in the regulation of neurodevelopment by serotonin. Here, we review the spatial and temporal expression patterns of 5-HT3 receptors in the pre- and early postnatal rodent brain and its functional implications. First, 5-HT3 receptors are expressed on GABAergic interneurons in neocortex and limbic structures derived from the caudal ganglionic eminence. Mature inhibitory GABAergic interneurons fine-tune neuronal excitability and thus are crucial for the physiological function of the brain. Second, 5-HT3 receptors are expressed on specific glutamatergic neurons, Cajal-Retzius cells in the cortex and granule cells in the cerebellum, where they regulate morphology, positioning and connectivity of the local microcircuitry. Taken together, the 5-HT3 receptor emerges as a potential key-regulator of network formation and function in the CNS, which could have a major impact on our understanding of neurodevelopmental disorders in which 5-HT plays a role.